The Creativity of Arabic Teachers in Designing Student Worksheet (LKPD) at Madrasah Ibtidaiyah - Fadhilah; Salma Hayati; Azizah; Aulia Rizki (South Sulawesi Education Development (SSED), 2024)
The purpose of this study is to describe the creativity of Madrasah Ibtidaiyah Arabic teachers in designing LKPD (student worksheet) for Arabic learning in Bireuen District, Aceh Province. The research focuses on three components of creativity: motivation, environment, and thinking style. This research is a quantitative study using questionnaires to obtain data. A total of 30 Arabic teachers as research samples were selected based on the western, central, and eastern zones in the Bireuen District area with 10 samples each. The data is analyzed in quantitative descriptive terms, namely percentage and average scores, using Statistical Package for Social Science (SPSS) version 20. The results of the study found that teacher creativity in the motivation aspect was moderate, the environmental aspect was medium, and the thinking style aspect was lacking. The overall analysis shows that the creativity of Arabic teachers in Madrasah Ibtidaiyah Bireuen District is in the medium category. This research provides valuable insights into the creativity of Arabic teachers at the Madrasah Ibtidaiyah level in designing LKPD. It can provide information to improve teacher creativity and the learning can be carried out properly and quality.